2021
DOI: 10.1101/2021.07.19.452977
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification and characterization of bacterial glycogen-degrading enzymes in the vaginal microbiome

Abstract: The healthy human vaginal microbiota is generally dominated by Lactobacilli, and the transition to a more diverse community of anaerobic microbes is associated with a number of health risks. While the mechanisms underlying the stability of Lactobacillus-dominated vaginal communities are not fully understood, competition for nutrients is a likely contributing factor. Glycogen secreted by epithelial cells is widely believed to support the growth of vaginal microbes. However, the mechanism by which bacteria acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 84 publications
0
10
2
Order By: Relevance
“…Third, having demonstrated significant levels of glycogen-degrading enzyme activity in biobanked vaginal samples, our work underlines the critical importance of cold chain management to ensure measured glycogen/maltodextrin levels reflect those present at the time of sample collection. Finally, in contrast with previous work, we found glycogen-degrading enzyme activities, including that of pullulanases, were abundant in vaginal swab supernatants and minimally present in the cell pellet [97]. Since N-terminal motifs in the L. crispatus PulA sequence are predicted to tether the protein to the outer membrane’s Surface Layer Protein A [97], it is possible that most PulA protein is cell surface-associated in vivo , but was perhaps dislodged through the vigorous vortexing performed during swab preparation.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Third, having demonstrated significant levels of glycogen-degrading enzyme activity in biobanked vaginal samples, our work underlines the critical importance of cold chain management to ensure measured glycogen/maltodextrin levels reflect those present at the time of sample collection. Finally, in contrast with previous work, we found glycogen-degrading enzyme activities, including that of pullulanases, were abundant in vaginal swab supernatants and minimally present in the cell pellet [97]. Since N-terminal motifs in the L. crispatus PulA sequence are predicted to tether the protein to the outer membrane’s Surface Layer Protein A [97], it is possible that most PulA protein is cell surface-associated in vivo , but was perhaps dislodged through the vigorous vortexing performed during swab preparation.…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, in contrast with previous work, we found glycogen-degrading enzyme activities, including that of pullulanases, were abundant in vaginal swab supernatants and minimally present in the cell pellet [97]. Since N-terminal motifs in the L. crispatus PulA sequence are predicted to tether the protein to the outer membrane’s Surface Layer Protein A [97], it is possible that most PulA protein is cell surface-associated in vivo , but was perhaps dislodged through the vigorous vortexing performed during swab preparation. Alternatively, PulA may be released from the cell wall in vivo through biological processes such as proteolytic activity.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A recent key study confirmed alpha-glucosidase activity of pullulanase genes from different vaginal bacteria by heterologous expression. It showed that the Lactobacillus crispatus pullulanase degrades glycogen, pullulan and amylose retaining activity at pH values that are common in a Lactobacillus -dominated vaginal environment [14]. L. crispatus strains isolated from low-glycogen environments, such as the human or poultry gut, more often lacked the pullulanase gene indicating niche-specificity [15].…”
Section: Introductionmentioning
confidence: 99%
“…Vaginal samples show alpha-glucosidase activity, which was postulated to be mostly of human origin on the basis of antibody [16,17] and proteomic analysis [18]. At the same time results from two studies have indicated that alpha-glucosidases in a subset of vaginal samples may be of bacterial origin on the basis of optimal pH and substrate and product profiling [14,19]. However, a metaproteomic study of vaginal lavages from women with a crispatus -dominated microbiome, failed to detect any L. crispatus pullulanase protein, which poses questions about host-related or genetic factors influencing its presence [18].…”
Section: Introductionmentioning
confidence: 99%